Developing iPad Application based on Video Modeling to Enhance Self-Protection Skills for Children with Autism Spectrum Disorder in Jeddah - Al-Talhi, Afnan Maatouk (Journal of Educational and Psychological Sciences, 2019)
The current study aimed to develop a mobile application based on video modeling to improve and enhance self-protection skills for children with autism. Semi-experimental design of the two groups was adopted: the control, which received the self-protection skills in the traditional way, while these skills was provided to the experimental group through the application based on video modeling. The research sample was consistedof 16 students who met the criteria. The researcher was applied the self-protection skills scale on the sample. After the experiment was applied for five weeks, the data were analyzed statistically. The results showed the effectiveness of the application in the development of self-protection skills for autistic children. The researcher recommended the use of the preferences of children with autism and the use of applications that based on video modeling in their education.
Keywords: iPad applications; video modeling; self-protection skills; autism